2004
DOI: 10.1136/adc.2002.012088
|View full text |Cite
|
Sign up to set email alerts
|

The siblings of childhood cancer patients need early support: a follow up study over the first year

Abstract: Background and methods:In a 1 year follow up study, we assessed the life situation of 33 siblings of childhood cancer patients and 357 healthy controls. The hypothesis was that siblings have more behavioural and health related problems just after the cancer diagnosis. Validated assessment methods were used. Results: Siblings below school age tended to have conduct problems, psychosomatic problems, and a mixed group of other behavioural problems, when assessed 3 months after the cancer diagnosis. These symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 20 publications
4
39
1
15
Order By: Relevance
“…Rehabilitation and support courses run for families with a child with cancer have reported a beneficial effect on parental adaptation and family cohesion with better adaptation of siblings [24,25]. A recent study in siblings of cancer patients has again emphasised the value of targeted, early information about the chronic illness and the value of educational support with school personnel being informed [26]. Our own strategy has been to involve schoolteachers within the renal unit to actively liase with the patient's school and with families in the clinic [27,28].…”
Section: Discussionmentioning
confidence: 98%
“…Rehabilitation and support courses run for families with a child with cancer have reported a beneficial effect on parental adaptation and family cohesion with better adaptation of siblings [24,25]. A recent study in siblings of cancer patients has again emphasised the value of targeted, early information about the chronic illness and the value of educational support with school personnel being informed [26]. Our own strategy has been to involve schoolteachers within the renal unit to actively liase with the patient's school and with families in the clinic [27,28].…”
Section: Discussionmentioning
confidence: 98%
“…Houtzager et al (2003Houtzager et al ( , 2004 found age-specific reactions to cancer, which suggests age of the sibling also influences healthy sibling outcomes. The time since diagnosis also influences healthy sibling outcomes (Alderfer et al, 2003;Hamama et al, 2000;Houtzager et al, 2003;Houtzager et al, 2004;Lähteenmäki et al, 2004). In addition to the healthy sibling's age and gender, Van Dongen-Melman et al (1995) found that the sibling's age at diagnosis also influenced healthy sibling outcomes.…”
Section: Sociodemographic Factors and Healthy Sibling Outcomesmentioning
confidence: 99%
“…French et al (2013) found that healthy siblings between 4 and 17 years from initial diagnosis missed significantly more days of school than their peers. Lähteenmäki et al (2004) found that 3 months and 1 year after diagnosis, school-aged healthy siblings exhibited more learning problems than their peers.…”
Section: Academic Outcomes In Children and Adolescencementioning
confidence: 99%
See 2 more Smart Citations